DPP-4 inhibitor anagliptin protects against hypoxia-induced cytotoxicity in cardiac H9C2 cells. Issue 1 (4th December 2019) - Ma, Yunxiang; Wang, Junkai; Wang, Changhua; Zhang, Qiong; Xu, Yannan; Liu, Huajin; Xiang, Xia; Ma, Jiangwei
Abstract: Cardiovascular complications are the leading cause of mortality and morbidity in type 2 diabetes patients. Diabetes greatly increases the risk of heart disease; therefore, the management of diabetes often involves the prevention of heart disease. DPP-4 inhibitors have been proven to be the effective therapeutic agents of glycaemic control. Recent studies have shown that certain types of DPP-4 inhibitors could also have cardiovascular benefits. In this study, we examined the protective role of the newly developed DPP-4 inhibitor anagliptin in cultured cardiac myocytic cell line H9C2 cells. Our data show that exposure of H9C2 cells to hypoxic conditions induced higher expression of DPP-4, indicating that DPP-4 is a hypoxia-inducible factor. The inhibition of DPP-4 by anagliptin ameliorates hypoxia-induced cytotoxicity and induction of the pro-inflammatory cytokines IL-6 and MCP-1. Anagliptin also suppresses hypoxia-induced oxidative stress as revealed by the detected levels of cellular ROS and reduced GSH. Moreover, anagliptin protects myocytes from hypoxia-associated reduced mitochondrial membrane potential. Mechanistically, we show that anagliptin promotes hypoxia-induced NFR2/HO1 induction but suppresses HMGB1 and MyD88 generation. Collectively, our data indicate that anagliptin-mediated DPP-4 inhibition is a protective mechanism in cardiomyocytes and imply that the DDP-4 inhibitor anagliptin plays dual roles by lowering glucose and protecting cardiomyocytes.